Realizing Intelligent Pedagogical Agents in Immersive Virtual Learning Environments - Soliman, M.; Guetl, Christian (Kassel University Press, 2010)
While Learners enjoy the sense of presence and rich visualization in 3D Immersive Virtual Learning Environments, they require more interactivity and pedagogical guidance. Intelligent Pedagogical Agents, IPAs, which are autonomous and intelligent software entities can provide such demands if they are employed in the VLE. Theyprovide interactivity (dialogues), increase motivation and engagement, support collaborative functions, provide tutorial support, and more. This paper discusses those aspects with educational grounds. Since our target is to practically employing IPAs in the Immersive VLE, the paper reviews the required elements of such integration, visits supporting models, architectures and standards. It discusses state of the art of IPA and Immersive VLE with future perspectives of such integration.